Indonesian Online Shopping Practices in the COVID-19 Pandemic Era: A Study of Culture and Cyber Security Law - Radius Setiyawan; Satria Unggul Wicaksana Prakasa (Universitas Ahmad Dahlan, 2021)
Introduction to the Problems: The condition during COVID-19 that made people doing more activities at home drove the increase in spending intensity. This condition referred to a new normal. Online shopping has long been a habit for some people because of the convenience provided. In conditions of increasing online shopping activities certainly have implications for the community—online shopping practices of Indonesian people in the Covid-19 pandemic era, with an approach and cybersecurity.Purpose/ Objective Study: This research aims to examine the relationship between online shopping practices of the Indonesian people in the Covid-19 pandemic era.Design/Methodology/Approach: With an approach to the study of culture and cybersecurity, with integration between culture studies, economy, and digital law studies.Findings: This research finds that massive online shopping practices in Indonesia have implications for social vulnerability. In a cultural context, people could get caught up in alienation. Online shopping activities as productive work (work to make commodities) alienate humans, four sides humans from themselves, productive work objects (instruments and productive work objects), and products consumed. While in the context of security, there was a risk of using misused personal data. It was necessary to ratify the Law of Personal Data Security as a legal regulation mechanism for sanctions for the data privacy misused in.Paper Types: Research article